2013
DOI: 10.1007/s10834-013-9362-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Conditions and Australian Financial Risk Attitudes, 2001–2010

Abstract: This paper employed panel data from the 2001-10 waves of the Household, Income, and Labor Dynamics in Australia (HILDA) survey to investigate the financial risk attitudes of 10,000 individuals across 6,839 households. Ordered logit models including individual and household random effects tested for changes in risk tolerance while focusing on the impact of transitory macroeconomic conditions and controlling for individual demographic and socioeconomic characteristics. We found Australians generally reduced thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…This reflects the overall flight to liquid cash style investments in 2010, as also shown in Table , where deposit holdings increased on average from $33,277 in 2006 to $47,429 in 2010, whilst the average equity holdings fell from an average of $63,118 to $47,285. The downward trend of risk aversion has been captured by West and Worthington () who found that Australian households generally reduced their tolerance for risk over time. However, as Figure demonstrates, there are significant outliers causing the distribution to be positively skewed, particularly in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the overall flight to liquid cash style investments in 2010, as also shown in Table , where deposit holdings increased on average from $33,277 in 2006 to $47,429 in 2010, whilst the average equity holdings fell from an average of $63,118 to $47,285. The downward trend of risk aversion has been captured by West and Worthington () who found that Australian households generally reduced their tolerance for risk over time. However, as Figure demonstrates, there are significant outliers causing the distribution to be positively skewed, particularly in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Researcher also shows that macroeconomic conditions also affect the risk tolerance level of respondent in the same as demographic and socioeconomic characteristics. [16] The researcher also says that financial literacy can also be defined as the ability to understand the financial terms and also the mathematical ability of the individual. For doing the research the researcher consider some factors as age, occupation, gender, ethnicity, income saving and debt.…”
Section: Retirement Planningmentioning
confidence: 99%
“…The above list is an indication of a potentially long and rich risk-oriented research agenda at the intersection of entrepreneurship and internationalization with advances in some and questions remaining in others. The reader is encouraged to consult the fastdeveloping literature addressing some of the above issues and questions (As starting point, for example see, Anderson et al 2009;Ball et al 2010;Etchart-Vincent et al 2011;Cheung et al 2013;Löhndorf, et al 2014;West et al 2014).…”
Section: Summary Highlight Of Articles Their Respective Linkages Andmentioning
confidence: 99%